A bilingual lexicon/glossary of neologisms from written business english sources for ecuadorian english teachers, translators, and students - Pareja Lalama, María Augusta (2017)
The basic premise of this dissertation is that English business vocabulary is always changing by the creation of neologisms; therefore, to help all people interested and who work with business English and related topics. The newly created words were collected, analyzed, and presented as documented additions to normal dictionaries. The dissertation starts with an introduction, which describes the topic, justification, approach and scope of the subject, as well as the background and objectives. The first chapter develops the theoretical framework and methodology. In the second chapter, the research methodology and collection of data are applied. The third chapter presents the author’s conclusions and recommendations. The study met the proposed objectives since fifty-three neologisms were identified with their Spanish and English meaning, probable formation analysis, and they are displayed in a glossary table to facilitate their use. As a result of this study, the author recommends that these efforts of collecting neologisms should be continued by the Faculty of Communication, Linguistics and Literature. The updates to this research should be published at least digitally because those involved in business English will take advantage of the Internet as a reference source. English Linguistics professors, as dissertation advisors, should encourage some of their students to pursue with this never-ending task, as a class exercise and a contribution that will make easier the work of English teachers, translators, and other students.